Difference in the songs of paired and unpaired southern yellow-cheeked gibbon males (Nomascus gabriellae): social status or age? - Hradec, Michal; Illmann, Gudrun; Prikrylová, Martina; Bolechová, Petra; Vostrá-Vydrová, Hana (Frontiers in Ecology and Evolution, 2023)
All gibbons (Primates: Hylobatidae) are well known for emitting loud vocalizations specific for species and sex. The songs of paired and unpaired male southern yellow-cheeked gibbons (Nomascus gabriellae) are characterized by the presence of staccato notes and multi-modulation phrases with two or more extremely rapid frequency modulations in the second note. In addition, paired males also produce a coda vocalization, which is similar to the multi-modulation phrase of male calls but lacks the staccato notes and always occurs directly following the female great call as part of a pair-specific duet. The aim of this study was firstly to assess whether the songs of paired and unpaired males can be acoustically distinguished from one another and secondly, whether the coda vocalization differs from the multi-modulation phrase of the male call in paired males. To assess these issues, we analysed 616 songs obtained from a long-term study of vocal development in 14 captive adult males (> 7 years old), half of whom were unpaired and significantly younger than paired subjects. For each song, we quantified nine acoustic features, for which we applied a suite of linear mixed effects models with social status as a fixed variable and age as a regression coefficient. This allowed us to compare (1) the structure of male calls (staccato notes and multi-modulation phrase) between paired and unpaired subjects, (2) the muti-modulation phrase of unpaired subjects to the coda vocalization of paired subjects, and (3) the multi-modulation phrase of paired males to the coda vocalization. We found that the male call of younger-unpaired subjects had a longer duration, broader frequency range, higher maximum frequency and fewer staccato notes than their counterparts in paired subjects. The coda vocalization of older-paired males exhibited a higher minimum frequency and a larger number of frequency modulations than the multi-modulation phrase of all males. While the male call of younger-unpaired males differs from both the male call and the coda vocalization of older-paired males, further studies are necessary to disentangle the effects of age and pairing status.